2015
DOI: 10.1371/journal.pone.0121166
|View full text |Cite
|
Sign up to set email alerts
|

Ornaments Reveal Resistance of North European Cultures to the Spread of Farming

Abstract: The transition to farming is the process by which human groups switched from hunting and gathering wild resources to food production. Understanding how and to what extent the spreading of farming communities from the Near East had an impact on indigenous foraging populations in Europe has been the subject of lively debates for decades. Ethnographic and archaeological studies have shown that population replacement and admixture, trade, and long distance diffusion of cultural traits lead to detectable changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 51 publications
1
51
0
1
Order By: Relevance
“…This is consistent with the idea that cultural diffusion may have been the dominant process of neolithization in that region. This idea is supported by a recent study of body ornaments at the time of the Neolithic transition of Europe, which showed continuity of Mesolithic body ornaments across the Neolithic transition in northern Europe, but not in southern and central Europe …”
Section: The Neolithic Transitionmentioning
confidence: 66%
“…This is consistent with the idea that cultural diffusion may have been the dominant process of neolithization in that region. This idea is supported by a recent study of body ornaments at the time of the Neolithic transition of Europe, which showed continuity of Mesolithic body ornaments across the Neolithic transition in northern Europe, but not in southern and central Europe …”
Section: The Neolithic Transitionmentioning
confidence: 66%
“…And indeed there is evidence that the peoples who around 5000 BC in Europe started with farming practices used ornaments that are different from ornaments used by those in the same region and time who remained hunter-gatherers (Solange, d'Errico & Vanhaeren, 2015). The latter people's ornaments consisted mainly of necklaces with animal teeth and punctured shells.…”
Section: Discussion: Another Formulation Personal Ornaments and Sky mentioning
confidence: 99%
“…In the area of present-day Poland ornaments made of fossil shells were found at archaeological sites, specifically in burials, related to Late Neolithic and Early Bronze Age societies such as the Lublin-Volhynia, Złota, Mierzanowice and Strzyżów (Figure 1 and Table 1) -Yosef Mayer, Bonsall, & Choyke, 2017;Bonnardin, 2009;Rigaud et al, 2015). As was previously noted, there are discernable regional patterns in the use of particular types of ornaments for body adornment, some of which persisted for several millennia (Rigaud et al, 2015;Vanhaeren & d'Errico, 2006). This can already be observed in the Palaeolithic period, for example, within Magdalenian entities in the Paris Basin (Peschaux et al, 2017).…”
Section: Fossil Shells and Archaeological Contextmentioning
confidence: 99%
“…The discussed types of shells, all characteristic for the European Neolithic (Bonnardin, 2009;Rigaud et al, 2015), were brought to the area of present-day Poland, and, at the same time, locally available raw materials were used to produce ornaments modelled on the imported items.…”
Section: Fossil Shells and Archaeological Contextmentioning
confidence: 99%